2013
DOI: 10.2147/ceg.s44700
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of inflammatory bowel disease-indeterminate from childhood to adulthood: within a 25 year period

Abstract: BackgroundInflammatory bowel disease (IBD)-indeterminate is a subgroup of IBD that has features of both ulcerative colitis (UC) and Crohn’s disease (CD).AimsTo determine the clinical course of IBD-indeterminate in children over a 25 year period.MethodsWe performed a retrospective investigation on children diagnosed with IBD. Diagnosis and disease distribution of IBD was based on clinical, radiologic, endoscopic, and histologic examinations.ResultsFour hundred and twenty children diagnosed with IBD between 1986… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…In other studies, 23-84% of patients with an initial diagnosis of IBD-U were later classified as UC or CD [9,12,24,[31][32][33]55]. In pediatric patients, a systematic review found an increase in diagnosis of CD over time, and a decrease in IBD-U [7].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In other studies, 23-84% of patients with an initial diagnosis of IBD-U were later classified as UC or CD [9,12,24,[31][32][33]55]. In pediatric patients, a systematic review found an increase in diagnosis of CD over time, and a decrease in IBD-U [7].…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of IBD-U is usually reported to be higher among pediatric patients compared to that of the adult population: 13 versus 6% in a meta-analysis [6], and to be decreasing over disease course [7]. In well characterized IBD cohorts, the proportion of IBD-U has been reported to range from 1 to 20% in adults [8][9][10][11][12][13][14][15][16][17][18][19][20] and from 4 to 22% in pediatric patients [21][22][23][24][25][26][27][28][29][30][31][32][33]) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, several endoscopic and microscopic CD manifestations exclude UC as a possible differential diagnosis. This explains why most follow‐up studies report that a significant proportion of patients with UC (or inflammatory bowel disease unclassified (IBDU)) will ultimately be re‐classified as having CD . It is probable that more frequent use of upper endoscopy, small bowel imaging and biopsy sampling in patients with adult‐onset IBD would increase the proportion diagnosed with CD rather than UC.…”
Section: Incidencementioning
confidence: 99%
“…В европейском согласительном документе [3] под-черкнуто, что у пациентов, у которых есть клинические признаки воспалительного заболевания, но нет четких макро-и/или микроскопических признаков язвенно-го колита или болезни Крона, может использовать-ся термин «воспалительное заболевание кишечника неклассифицированное» (Inflammatory bowel disease unclassified, IBD-U). Ряд исследователей склонны счи-тать, что вариант IBD-U является отдельным фенотипом заболевания с особенностями клинической манифеста-ции симптомов в возрастном аспекте [6] распростра-ненности патологического процесса в кишечнике [7], длительного (годами) сохранения фенотипа [8] и более неблагоприятного прог ноза [9].…”
Section: Introductionunclassified
“…В биохимическом анализе сыворотки крови име-лась диспротеинемия: альбумин 48,98% (норма 53,0-68,0), альфа-1 глобулин -6,26% (норма 1,6-4,5), аль-фа-2 -23,01% (норма 5,7-11,5), бета -12,05% (норма 8,0-14,2), гамма -9,70% (норма 10, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]5).…”
Section: Introductionunclassified